Single-layer graphene-assembled 3D porous carbon composites with PVA and Fe3O4 nano-fillers: an interface-mediated superior dielectric and EMI shielding performance - Rao, B. V. Bhaskara; Yadav, Prasad; Aepuru, Radhamanohar; Panda, H. S.; Ogale, Satishchandra; Kale, S. N. (Physical Chemistry Chemical Physics, 2015)
In this study, a novel composite of Fe3O4 nanofiller-decorated single-layer graphene-assembled porous carbon (SLGAPC) with polyvinyl alcohol (PVA) having flexibility and a density of 0.75 g cm(-3) is explored for its dielectric and electromagnetic interference (EMI) response properties. The composite is prepared by the solution casting method and its constituents are optimized as 15 wt% SLGAPC and 20 wt% Fe3O4 through a novel solvent relaxation nuclear magnetic resonance experiment. The PVA-SLGAPC-Fe3O4 composite shows high dielectric permittivity in the range of 1 Hz-10 MHz, enhanced by a factor of 4 as compared to that of the PVA-SLGAPC composite, with a reduced loss by a factor of 2. The temperature dependent dielectric properties reveal the activation energy behaviour with reference to the glass transition temperature (80 degrees C) of PVA. The dielectric hysteresis with the temperature cycle reveals a remnant polarization. The enhanced dielectric properties are suggested to be the result of improvement in the localized polarization of the integrated interface system (Maxwell-Wagner-Sillars (MWS) polarization) formed by the uniform adsorption of Fe3O4 on the surface of SLGAPC conjugated with PVA. The EMI shielding property of the composite with a low thickness of 0.3 mm in the X-band (8.2-12.4 GHz) shows a very impressive shielding efficiency of similar to 15 dB and a specific shielding effectiveness of 20 dB (g cm(-3))(-1), indicating the promising character of this material for flexible EMI shielding applications.